Multivariate data analysis for semen quality in two frog species (Research, Society and Development, 2024)
Despite the growing body of research on frog reproduction and semen quality, studies employing statistical methods and analyses are scarce. The present study aimed to examine the use of exploratory multivariate data analysis for evaluating the seminal quality of frogs, determining a possible hierarchy among frog species based on semen characteristics, and identifying the most effective clustering strategy. Data on the seminal quality of the butter frog (Leptodactylus ocellatus, native specie) were collected from seven samples, and for the bullfrog (Lithobates catesbeianus, exotic specie), five samples were used, all derived from a literature review. Four distinct clustering strategies were tested: Single Linkage, Unweighted Pair Group Method with Arithmetic Mean (UPGMA), Complete Linkage, and Ward’s method. Exploratory multivariate data analysis could effectively evaluate frog seminal quality, allowing the classification of frog species (both native and exotic) based on semen. Among the tested strategies, UPGMA emerged as the most suitable grouping method.